Laparoscopic Management of Dermoid Cyst of Ovary is a Safe Procedure - Joshi, Arun Prasad; Chitrakar, Neer Shobha; Thapa, Bimal Kumar; Pariyar, Jitendra; Shrestha, Isha; Maharjan, Rima; Maharjan, Pabitra; Dahal, Sudip Chandra (Journal of Nepal Health Research Council, 2021)
Background: Dermoid cyst, a common benign neoplasm of ovary in women, needs treatment because of the risk of torsion, rupture, and malignant change. Laparoscopic surgery nowadays is the preferred treatment modality, but the only issue is its safety in case of rupture and spillage of its contents with the risk of chemical peritonitis and malignant dissemination. Aim of the study was to find out the safety of laparoscopic surgery for dermoid cyst of ovary.Methods: It was a retrospective study done from January 2017 to December 2019. All the women with diagnosis of dermoid cyst of ovary managed laparoscopically either salpingoophorectomy or cystectomy were taken into study. Analysis of size of the cyst operated, the time taken, spillage rate, duration of hospital stay, and post-operative complications especially chemical peritonitis was done.Results: There were 61 women who had undergone laparoscopic surgery. Laparoscopic cystectomy was done in 68.9% (n=42), laparoscopic salpingoophorectomy in 29.5% (n=18). Mean age of the patient was 31.74±8.38 years. Mean size was 6.21±1.99 cm. Rupture and spillage were observed in 21.3% (n=13) that were > 5cm in diameter (X2= 3.62, p=0.05). Larger the size of the cyst, more the surgical time was noted (X2=6.26, p=0.04). Significant difference in mean operating time in case of cyst rupture and spillage (p=0.004) was observed. Mean hospital stay was 53.5±1.3 hours. No case of chemical peritonitis was observed with spillage. All cases had histopathology of mature cystic teratoma.Conclusions: Laparoscopic surgery is safe for dermoid cyst of ovary even with rupture and spillage of its contents.Keywords: Dermoid cyst; laparoscopy; spillage